Resurgence of Ebola Virus: Transmission, Pathogenesis, Prevention and Cure - Reem M. Aljowaie, (Pakistan Journal of Medical & Health Sciences, 2023)
Ebola virus (EBOV) disease is a zoonotic disease that is caused by four species of genus Ebolavirus. The EBOV disease has outbreaks (1976-2022) in West and Central African countries, high mortality rate has made it a public health concern. EBOV is a filamentous virus having negative stranded and non-segmented RNA. The EBOV genome has the unique capability of forming soluble glycoprotein. Since its first emergence in human history, several effective therapeutics and vaccines are developed. These vaccines include replicative or non-replicative vectored vaccines, DNA vaccines and monovalent or polyepitopic vaccines. This article reviewed the structure of EBOV and pathophysiology as well as the immune response of EBOV infection. In addition to diagnosis and vaccinations available to cure EBOV at acute and chronic stages. Keywords: Zoonotic disease, Filovirus, Soluble glycoprotein, DNA vaccines, Polyepitopic, Vectored vaccines, Pathophysiology, Immune response